2020
DOI: 10.1002/jbmr.4286
|View full text |Cite
|
Sign up to set email alerts
|

Compressive Strength of Iliac Bone ECM Is Not Reduced in Osteogenesis Imperfecta and Increases With Mineralization

Abstract: Osteogenesis imperfecta (OI) is an inheritable, genetic, and collagen-related disorder leading to an increase in bone fragility, but the origin of its "brittle behavior" is unclear. Because of its complex hierarchical structure, bone behaves differently at various length scales. This study aims to compare mechanical properties of human OI bone with healthy control bone at the extracellular matrix (ECM) level and to quantify the influence of the degree of mineralization. Degree of mineralization and mechanical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 41 publications
3
21
0
Order By: Relevance
“…By contrast, higher Young’s modulus, hardness, and dissipated energy of bone at the extracellular matrix level are observed in the iliac crest of human OI patients than in healthy bone. The compressive strength of iliac bone at the extracellular matrix level does not show dramatic decrease compared to healthy bone . Mineralized fibrils in healthy murine bone show strain-rate dependent stiffening.…”
Section: Hierarchical Structure and Deformation Mechanisms Of Bonementioning
confidence: 89%
See 1 more Smart Citation
“…By contrast, higher Young’s modulus, hardness, and dissipated energy of bone at the extracellular matrix level are observed in the iliac crest of human OI patients than in healthy bone. The compressive strength of iliac bone at the extracellular matrix level does not show dramatic decrease compared to healthy bone . Mineralized fibrils in healthy murine bone show strain-rate dependent stiffening.…”
Section: Hierarchical Structure and Deformation Mechanisms Of Bonementioning
confidence: 89%
“…The compressive strength of iliac bone at the extracellular matrix level does not show dramatic decrease compared to healthy bone. 99 Mineralized fibrils in healthy murine bone show strain-rate dependent stiffening. By contrast, the fibrillar stiffening mechanism is absent in the steroid induced osteoporosis murine model.…”
Section: Microscopic Bone Deformation Andmentioning
confidence: 99%
“…Numerous studies have reported modified whole-bone-level mechanics of OI bone, including decreased compressive elastic modulus, reduced bending strength, increased compressive strength, increased hardness, and, most notably, heightened brittleness compared to healthy counterparts [142,143,152,153]. For smaller length scales, an increased compressive modulus was found in the extracellular matrix of OI bone compared to WT using FIB-machined micropillar samples, and the magnitude of increase appeared to correlate with the degree of bone mineralization and disease severity (Figure 5c) [46]. In another recent study, by subjecting OIM bone to ex-situ micropillar compression tests and through finite element modeling, Maghsoudi-Ganjeh et al proposed the possible mechanical behavior of OI bone at the fibrillar level [153].…”
Section: Osteogenesis Imperfectamentioning
confidence: 95%
“…Compressive strength of bone was found to increase with OI severity. Figures reprinted with permission from [46].…”
Section: Osteogenesis Imperfectamentioning
confidence: 99%
See 1 more Smart Citation